An examination of general, nondestination-specific versus destination-specific motivational factors - Gursoy, D; Bonn, M.; Chi, C. (Routledge, 2010)
This article examines the impacts of general, nondestination-specific motivational factors and destination-specific motivational factors on travelers' decisions to visit a destination. Data for this study was collected from visitors to four key cultural heritage attractions in Tampa, Florida during 2006 through personal interviews. Using structural equation modeling, data was analyzed to identify the motivational factors that were likely to influence travelers' cultural heritage visitation pattern. Findings suggest that 3 of 7 motivational factors examined in this study are likely to have significant influences on cultural heritage site visitation patterns. Both interest in historic sites and interest in culture are found to have a positive impact, while relaxation is found to have a negative impact. Findings also suggest that climate, shopping, fun and sand, and outdoor and leisure do not have any significant impact on cultural heritage site visitation patterns of travelers. © Taylor & Francis Group, LLC.